(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2014)
An efficient protocol was established for in vitro shoot multiplication of the biodiesel plant, Jatropha curcas L. (Euphorbiaceae) through direct organogenesis using shoot tip and nodal explants. Best shoot induction was observed on MS basal medium supplemented with 1.5 mg/l BAP + 0.5 mg/l NAA, in which 86.2% of nodal explants responded to produce maximum number (7.2 ± 0.68) of shoots per culture. In vitro raised shoots rooted on half strength MS medium with 1.0 mg/l IAA. The survival rate of regenerated plantlets was 85%. DOI: http://dx.doi.org/10.3329/bjsir.v49i1.18854 Bangladesh J. Sci. Ind. Res. 49(1), 41-46, 2014